A gas chromatographic and spectrophotometric-based assessment of an oral preparation from a traditional exhilarating formulation; linking Persian medicine to the modern phytopharmaceuticals - Ali Sahragard; Aida Alipour; Mohammad M. Zarshenas (Exploration of Drug Science, 2025)
Aim: Depression is one of the most important mental diseases. Different pharmacological and non-pharmacological methods are used to treat depression. Traditional and complementary medicine also have a special role in the treatment of depression. Among the specific medicinal formulations mentioned in Traditional Persian Medicine (TPM), an important and widely used form is “Mufarrah” (exhilarating), which indirectly refers to the mood-stabilizing group. In this work, a related traditional formulation has been reformulated and standardized as a conventional tablet. Methods: A simple and famous example among this group is “Mufarrah-e-Bared-e-Saghir”, containing Rosa × damascena Herrm., Coriandrum sativum L., Melissa Officinalis L. Following tablet preparation of the mentioned remedy, total phenolic and flavonoid content was determined using the spectrophotometric method. Volatile constituent analysis and quantification of linalool as the main component were carried out via gas chromatography (GC) [GC/MS (mass spectrometry) and GC/FID (flame ionization detector)]. Results: According to the results, the main compound of the final product was linalool (54.6%). Linalool, total phenol, and total flavonoid amounts have been calculated, respectively, 2,379.65 ± 262.13 µg/mL of the extracted essential oil, 163.23 ± 0.61, and 41.41 ± 2.3 mg/g extract. Conclusions: Prepared tablets as a reformulated traditional medicine product with rich total phenols and flavonoids, as well as the presence of linalool as a considerable icon with antidepressant activities, can be introduced to the Persian medicinal plants market to control depression.